2016
DOI: 10.1155/2016/4978973
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Outcomes of Vitreoretinal Surgery after Traumatic Retinal Detachment

Abstract: Traumatic retinal detachments are a significant cause of morbidity. There are currently no evidence-based guidelines on the appropriate time to perform vitreoretinal surgery to repair a traumatic retinal detachment. Early intervention, within seven days of the inciting trauma, may decrease proliferative vitreoretinopathy and postoperative endophthalmitis. Later intervention may yield a reduced risk of inflammation and hemorrhage, particularly in cases of concomitant open globe injuries. This article reviews th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…9 Postoperative visual outcomes vary widely; however, attachment of the macula at presentation has been associated with a higher postoperative visual acuity and a poorer visual acuity at presentation is associated with a lower postoperative visual acuity. 9 Pediatric patients who had anatomical success during retinal detachment surgery correlated with higher postoperative visual acuity. 6 Our patient surprisingly still had a macula-on retinal detachment despite being 1 month after his injury and onset of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…9 Postoperative visual outcomes vary widely; however, attachment of the macula at presentation has been associated with a higher postoperative visual acuity and a poorer visual acuity at presentation is associated with a lower postoperative visual acuity. 9 Pediatric patients who had anatomical success during retinal detachment surgery correlated with higher postoperative visual acuity. 6 Our patient surprisingly still had a macula-on retinal detachment despite being 1 month after his injury and onset of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A review study reported that the anatomical success was not significantly related to the timing of intervention; however, there are insufficient data to conclude whether early or delayed surgery leads to improved outcomes at long-term follow-up. 18 Both the methods have a specific effect on vision improvement; postoperative BCVA of the SO group was significantly better than that of the FCVB group. Retinal reattachment is a prerequisite for vision recovery.…”
Section: Discussionmentioning
confidence: 87%
“…A review study reported that the anatomical success was not significantly related to the timing of intervention; however, there are insufficient data to conclude whether early or delayed surgery leads to improved outcomes at long-term follow-up. 18 …”
Section: Discussionmentioning
confidence: 99%
“…In our study, a considerable number of patients were classified as having complex RD, including those with macular hole (n = 18), complex cataract (n = 26), previous filtering glaucoma surgery (n = 13), chronic RD (n = 9), traumatic RD (n = 43), giant retinal tear (n = 21), total RD (n = 42) and vitreous haemorrhage (n = 82). Some of these factors have been shown to increase the risk of surgical failure, and this may explain our higher recurrence rates [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%